Formation of the black hole in Nova Scorpii - Podsiadlowski, P; Nomoto, K; Maeda, K; Nakamura, T; Mazzali, P; Schmidt, B (Institute of Physics Publishing, 2002)
Israelian and coworkers showed that the stellar companion of the black hole binary Nova Sco is polluted with material ejected in the supernova that accompanied the formation of the black hole primary. Here we systematically investigate the implications of these observations for the black hole formation process. Using a variety of supernova models, including standard as well as hypernova models (for different helium star masses, explosion energies, and explosion geometries) and a simple model for the evolution of the binary and the pollution of the secondary, we show that most of the observed abundance anomalies can be explained for a large range of model parameters (apart from the abundance of Ti). The best models are obtained for He star masses of 10-16 M⊙, where spherical hypernova models are generally favored over standard supernova ones. Aspherical hypernova models also produce acceptable fits, provided there is extensive lateral mixing. All models require substantial fallback and that the fallback material either reached the orbit of the secondary or was mixed efficiently with material that escaped. The black hole therefore formed in a two-step process, where the initial mass of the collapsed remnant was increased substantially by matter that fell back after the initial collapse. This may help to explain the high observed space velocity of Nova Sco either because of a neutrino-induced kick (if a neutron star was formed first) or by asymmetric mass ejection in an asymmetric supernova explosion.